Supporting Hierarchy and Heterogeneous Interfaces in Multi-Hop Wireless Ad Hoc Networks - Broch, Josh; Maltz, Dave; Johnson, David B. (Proceedings of the Workshop on Mobile Computing held in conjunction with the International Symposium on Parallel Architectures, Algorithms, and Networks, 1999)
Much progress has been made toward solving the problem of routing packets inside an ad hoc network, but there are presently no complete proposals for connecting ad hoc networks together to form larger networks, or for integrating them with wired internets. This paper describes a technique that allows a single ad hoc network to span across heterogeneouslink layers. Using this technique, we can both integrate ad hoc networks into the hierarchical Internet and support the migration of mobile nodes from the Internet into and out of ad hoc networks via Mobile IP. Taken together, these solutions improve the scalability of flat ad hoc networks by introducing hierarchy, and they enable all nodes participating in the ad hoc network to be reachable from anywhere in the world. We have implemented each of the solutions in a real testbed of 8 nodes using the Dynamic Source Routing (DSR) protocol. Generalizing our solutions, we describe several abstract scenarios and present our ideas for solving them